Humanized VHH-hFc Fusion Proteins Targeting the L-HN Fragment of Tetanus Toxin Provided Protection In Vivo - Yating Li; Kexuan Cheng; Jiazheng Guo; Yujia Jiang; Qinglin Kang; Rong Wang; Peng Du; Chen Gao; Yunzhou Yu; Zhixin Yang; Wei Wang; Jiansheng Lu (Antibodies)
Background: Tetanus toxin, produced by Clostridium tetani, is the second deadliest known toxin. Antibodies capable of neutralizing tetanus toxin (TeNT) are vital for preventing and treating tetanus disease. Methods: Herein, we screened thirty-six single variable domains on a heavy chain (VHHs) binding to the light chain (L) and the translocation domain (HN) (L-HN) fragment of TeNT from a phage-display library. Then, the L-HN-specific clones were identified, humanized, and fused with a human fragment crystallizable region (hFc) to form humanized VHH-hFc fusion proteins. Results: The humanized VHH-hFc fusion proteins TL-16-h1-hFc, TL-25-h1-hFc, and TL-34-h1-hFc possessed potent efficacy with high binding affinity, specificity, and neutralizing activity. Only 0.3125 μg was required for TL-16-h1-hFc or TL-25-h1-hFc, and 0.625 μg was required for TL-34-h1-hFc to provide full protection against 10 × Lethal Dose 50 (LD50) TeNT. In the prophylactic setting, 125 μg/kg of TL-16-h1-hFc or TL-25-h1-hFc provided full protection even when they were injected 12 days before exposure to 10 × LD50 TeNT, while TL-34-h1-hFc was less effective. In the therapeutic setting, 25 μg/kg of TL-16-h1-hFc or TL-25-h1-hFc could provide complete protection when administered 24 h after exposure to 5 × LD50 TeNT, while TL-34-h1-hFc required 50 μg/kg. Conclusion: Our results suggest that TL-16-h1-hFc, TL-25-h1-hFc, and TL-34-h1-hFc provide a bright future for the development of anti-TeNT preventive or therapeutic drugs.